Implementasi Penataan Ruang dan Wilayah Perkotaan di Kecamatan Mijen Kota Semarang - Devonda Ayesha Akbar; Yuwanto .; Lusia Astrika (Journal of Politic and Government Studies, 2014)
Semarang city is one city that has a high population is 1.558.380 people. Currently, with the availability of land in the city of Semarang is inversely proportional. So the population of Semarang is high but the availability of land is limited. So the government's efforts in addressing the problem of Semarang is to shape the development of sub-centers in the region such as in Sub Mijen Semarang. Semarang City Government has made a policy in the form of Regulation (Regulation) No 14 of 2004 on Spatial Plan Details section of Semarang City region in Sub Mijen Section IX.The purpose of this study to determine the implementation of spatial planning and urban areas in the district Mijen Semarang, factors supporting and inhibiting factors in the implementation. The method of this study used a qualitative descriptive approach-analytic. There are 4 variables in seeing the implementation of spatial planning, namely the content and context of the policy, the purpose and function of land use, land use, and land use control system.Factors supporting the implementation of the arrangement of space and territory in the district of Semarang Mijen include the presence of a clear policy, availability of environmental data and geological information; commitment from policy implementers; cooperation between government agencies, private sector, and communities; and budget. While the obstacles to implementation is communication, government oversight Semarang, unresolved land acquisition,2and lack of support from the local community towards the development ofconstruction in the District Mijen Semarang.Implementation of Spatial Planning and Urban Area in District MijenSemarang assessed effectively. However, the need for improvements in thesupervision of the government of Semarang. So, we need the cooperation by allagencies, private sector, and communities to be going according to plan that is inthe form of regulatory policy area No. 14 of 2004.Keywords: Implementation, Spatial planning, City of Satellites BSB, Control Space